Microbiological monitoring as a component of efficient prevention and treatment of purulent-septic infections in an orthopedics and traumatology department - N. M. Polishchuk; D. L. Kyryk; I. Ye. Yurchuk (Zaporožskij Medicinskij Žurnal)
Efficient monitoring of circulating purulent-septic infectious agents in a clinical setting and a study on antibiotic susceptibility of isolated strains of microorganisms allows identifying changes in the pathogen structure and trends in antibiotic resistance development, which helps to determine the tactics of antibacterial therapy and elaborate appropriate measures.